Evaluating antibody mediated opsonophagocytosis of bacteria via lab protocol: RAW 264.7 cell phagocytosis assay - Matthew Slarve; Travis Nielsen; Dongran Yu; Jordyn VanOrman; Brian Luna; Brad Spellberg (PLoS ONE, 2025)
Assessing the phagocytosis of microbes by macrophages is an important component of studies of novel immunotherapeutics, antimicrobial drugs, immune effectors, or any immunology related research. Here we define two protocols for measuring in vitro phagocytosis by RAW 246.7 cells – a photographic phagocytosis assay that allows optical measurement of bacterial cells inside of the RAW 246.7 cell by staining fixed cells and visually quantifying the bacteria that have been phagocytosed, as well as a killing assay, which measures the viable bacteria released from lysed cells following exposure and phagocytosis via colony forming unit analysis. These methods differ from previously available protocols for measuring phagocytosis, as they are more generalizable to a variety of microbes and experimental designs and use readily available cell lines and materials to produce robust results. We demonstrate the utility of our methods by showing how opsonization by our novel, therapeutic monoclonal antibodies drive phagocytosis and killing of the gram-negative bacteria, Acinetobacter baumannii.